Recommended practice for fiber-reinforced polymer products for overhead utility line structures : MOP 104 - Fecht, Galen (American Society of Civil Engineers, 2019)
"MOP 104, Second Edition, provides updated best practices and design recommendations for the use of fiber-reinforced polymer (FRP) composite poles and cross-arms in conductor support applications"-- Provided by publisher
Keywords: Electric lines -- Poles and towers -- Design and construction.; Electric lines -- Poles and towers -- Materials.; Fiber-reinforced plastics.; elektronické knihy; electronic books